Penerapan Good Corporate Governance Terhadap Kinerja Keuangan Pada Perbankan Syariah Yang Terdaftar Di Pasar Modal Syariah - Safira Rizki Mawaddah; Muhammad Salman; Nasrul Kahfi Lubis (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
This research aims to determine the influence of Good Corporate Governance on the financial performance of sharia banking listed on the Sharia Capital Market or the Indonesian Stock Exchange (BEI) for the 2016-2020 period. In this study, a purposive sampling technique was used in sampling so that a sample of 11 sharia banking companies was obtained. The type of data used in this research is secondary data which is then assisted by using the SPSS application to carry out data analysis techniques. And in measuring financial performance using Return On Assets (ROA). The results of this research can be concluded that Institutional Ownership has a significant effect on the financial performance of Islamic banking based on multiple linear analysis tests. The results also show that the Independent Board of Commissioners has a significant influence on the financial performance of sharia banking. And the audit committee also has a significant influence on the financial performance of sharia banking. The limitations of the research are the limited information published by sharia banking so that some of the population cannot be used as research samples and the research period is relatively short, namely only 5 years so that the research carried out by researchers does not reflect the long-term condition of the company and the data obtained is still not optimal. Suggestions for future researchers are to take a longer research period so that the data obtained can be more optimal.